Oscillation criteria for quasilinear elliptic equations of second order - Xu, Zhiting (Utilitas Mathematica, 2006)
By using auxiliary functions and weighted averaging technique, some oscillation criteria, for quasilinear elliptic equation of second order Σi, j=1N Di[Aij(x)|Dy| p-2Djy] + p(x) ∫(y) = 0 (E) are obtained. These criteria are extensions of the results due to Coles and Wintner for second order linear ordinary differential equation.